Research on HILS Technology Applied on Aircraft Electric Braking System - Suying Zhou; Hui Lin; Bingqiang Li (Journal of Electrical and Computer Engineering)
On the basis of analyzing the real-time feature of hardware-in-the-loop simulation of aircraft braking system, a new simulation method based on MATLAB/RTW (Real-Time Workshop) and DSP is introduced. The purpose of this research is to develop a digital control unit with antilock brake system control algorithm for aircraft braking system using HILS. DSP is used as simulator. Using this method, a detailed mathematical modeling of system is proposed first. Studies on reducing sampling time with model simplification and modeling for applying to I/O interface of DSP and HILS are conducted. Compared with other methods, this method is low cost and convenient to implement. By using these methods, we can complete HIL simulation of aircraft braking under various experimental conditions, modify its control laws, and test its braking performance. The results have demonstrated that this platform has high reliability. The algorithm is verified by real-time closed loop test with HILS system and the results are presented.